Case Report: Medullary carcinoma of the pancreas with MLH1 promoter hypermethylation, induced deficient mismatch repair, successfully treated with an immune checkpoint inhibitor - Ohtsubo, Koushiro; Sato, Shigeki; Sakaguchi, Hiroyuki; Kotani, Hiroshi; Nishiyama, Akihiro; Yamashita, Kaname; Yano, Seiji; Toshima, Fumihito; Inoue, Dai; Gabata, Toshifumi; Ikeda, Hiroko; Watanabe, Atsushi; et al. (Frontiers in Oncology, 2025)
We report the case of a 75-year-old woman with a pancreatic body mass. Pathological findings from endoscopic ultrasonography-guided fine-needle aspiration revealed medullary carcinoma of the pancreas (MCP). Deficient mismatch repair (dMMR) and high microsatellite instability (MSI-H) were identified through immunohistochemistry and next generation sequencing, respectively. While immunohistochemistry suggested MLH1 abnormality, no MLH1 mutation was; hypermethylation of the MLH1 promoter was later confirmed via bisulfite sequencing. The patient initially received nab-paclitaxel plus gemcitabine, achieving tumor shrinkage. Upon tumor regrowth, she was treated with the anti-programmed cell death-1 immune checkpoint inhibitor (ICI) pembrolizumab, which resulted in significant tumor reduction. This is the first case report of MCP with dMMR/MSI-H due to MLH1 promoter hypermethylation, effectively treated with an ICI.